Fewer new species colonize at low frequency N addition in a temperate grassland. (19th November 2015) - Zhang, Yunhai; Stevens, Carly J.; Lü, Xiaotao; He, Nianpeng; Huang, Jianhui; Han, Xingguo
Summary: Biologically reactive nitrogen (Nr) enrichment threatens biodiversity in diverse ecosystems. Previous controlled N addition experiments may overestimate the effects of atmospheric Nr deposition on the rate of species loss, as it has been found that low frequency Nr additions, as used in traditional studies, lead to more rapid biodiversity loss. It remains unclear, however, whether the colonization of new species (gain) or extinction of old species (loss) is the cause of this difference. By independently manipulating the frequency (twice vs. monthly additions year −1 ) and the rate (from 0 to 50 g N m −2 year −1 ) of NH4 NO3 inputs for six years in a temperate grassland of northern China, we aimed to examine the contribution of gain and loss of species to the reduction in species richness under different regimes of Nr inputs. Results showed that the gain of new species was higher at a high frequency of N addition than that at a low addition frequency, while loss of existing species was similar between the two frequencies of N addition. The number of new species gained decreased and old species lost increased with the increasing rate of Nr addition at both annual and five‐year intervals. Cumulative gain of new species was negatively correlated with soil acidification, ammonium concentration and community biomass accumulation, whereas cumulative loss of old species was positively correlated with these variables. Our results revealed lower new species colonization results in lower species richness at low frequency of Nr addition. Findings from this study highlight the important role of N addition frequency in regulating the effects of Nr addition on community dynamics. To assess the effects of atmospheric Nr deposition on ecosystem structure and functioning, it is necessary to assess not only the dose but also the frequency of N addition. Abstract : Lay Summary